Flux composition, solder composition, and electronic board
Patent Information
- Application Number
- JP2023119339
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-07-21
AI Technical Summary
【0007】 本発明の一態様によれば、イオン性清浄度が良好であり、水系洗浄剤でのフラックス残さの洗浄性に優れ、かつボイドを十分に抑制できるフラックス組成物、はんだ組成物、並びに、電子基板を提供できる。
Smart Images

Figure 0007645043000001 
Figure 0007645043000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a flux composition, a solder composition, and an electronic board. [Background technology]
[0002] The solder composition is a mixture of solder powder and a flux composition (rosin resin, activator, solvent, etc.) kneaded into a paste (see Patent Document 1). This solder composition is required to have printability, solderability, viscosity stability, and the like, as well as suppression of voids. In addition, when soldering is performed using a solder composition, flux residue remains around the joint after soldering. This ionic residue contains activator components, etc., and there is a concern that moisture may enter the residue distributed across the electrodes due to condensation, which may cause ionic migration. Therefore, it is desirable to have as little ionic residue as possible that may cause ionic migration. This can be evaluated by ionic cleanliness.
[0003] On the other hand, when reliability is important, the flux residue may be removed by cleaning after bonding. Traditionally, cleaning agents mainly composed of organic solvents with high cleaning power have been used for cleaning. However, cleaning agents with a high solvent content are subject to stricter regulations from the viewpoints of preventing water pollution, fire and air pollution, as well as from the viewpoint of occupational health. In recent years, the amount of solvent used has been reduced and cleaning agents mainly composed of water have been used. The use of such water-based cleaning agents has led to a worsening tendency in the cleaning performance of flux residue, which has become a problem. This tendency is particularly pronounced under parts with narrow gaps, where the flow of the cleaning agent is likely to be stagnant. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5887330 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a flux composition, a solder composition, and an electronic board which have a good ionic cleanliness, excellent cleaning properties for flux residues with an aqueous cleaner, and can sufficiently suppress the generation of voids. [Means for solving the problem]
[0006] According to the present invention, there are provided a flux composition, a solder composition, and an electronic board as described below. [1] A flux composition comprising: (A) a resin; (B) an activator; (C) a solvent; and (D) a thixotropic agent, The component (B) contains (B1) a dicarboxylic acid having 9 to 22 carbon atoms, The component (C) contains (C1) a solvent having a boiling point of 250° C. or lower and a melting point of 15° C. or higher, The blending amount of the (C1) component is 10% by mass or more and 50% by mass or less with respect to 100% by mass of the (C) component. Flux composition. [2] The flux composition according to [1], The component (B1) contains a dicarboxylic acid having 20 carbon atoms. Flux composition. [3] The flux composition according to [1] or [2], The component (C1) contains at least one selected from the group consisting of 1,4-butanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, and 2,5-dimethyl-2,5-hexanediol. Flux composition. [4] The flux composition according to any one of [1] to [3], The blending amount of the (D) component is 2% by mass or more and 20% by mass or less with respect to 100% by mass of the flux composition. Flux composition. [5] The flux composition according to any one of [1] to [4], Further, the polyisobutylene-containing Flux composition. [6] A flux composition according to any one of [1] to [5] and (E) a solder powder. Solder composition. [7] [6] A soldered portion using the solder composition according to the present invention. Electronic board. Effect of the Invention
[0007] According to one aspect of the present invention, it is possible to provide a flux composition, a solder composition, and an electronic board that have good ionic cleanliness, excellent cleaning properties for flux residues with an aqueous cleaner, and can sufficiently suppress voids. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Flux composition] First, the flux composition according to this embodiment will be described. The flux composition according to this embodiment is a solder composition other than the solder powder, and contains (A) resin, (B) activator, (C) solvent, and (D) thixotropic agent, which will be described below. The (B) component contains (B1) dicarboxylic acid having 9 to 22 carbon atoms, and the (C) component contains (C1) a solvent having a boiling point of 250°C or less and a melting point of 15°C or more. Furthermore, the blending amount of the (C1) component must be 10% by mass or more and 50% by mass or less with respect to 100% by mass of the (C) component.
[0009] The reasons why the flux composition according to the present embodiment has a good ionic cleanliness, is excellent in cleaning properties for flux residues with an aqueous cleaner, and can sufficiently suppress voids are not necessarily clear, but the inventors speculate as follows. That is, first, the ionic cleanliness is better when the components in the flux residue are less soluble in water or isopropanol. On the other hand, the cleaning property with an aqueous cleaning agent is better when the components in the flux residue are more soluble in an aqueous cleaning agent. Therefore, it is very difficult to achieve both the ionic cleanliness and the cleaning property with an aqueous cleaning agent. In contrast, in the flux composition according to the present embodiment, the dicarboxylic acid (B1) having 9 to 22 carbon atoms is used to solve the above two problems that are difficult to achieve at the same time. In addition, by using a predetermined amount or more of the solvent (C1) having a boiling point of 250°C or less and a melting point of 15°C or more, voids can be sufficiently suppressed. On the other hand, if the amount of the component (C1) is less than the predetermined amount, there is no adverse effect on the ionic cleanliness or the cleaning property with an aqueous cleaning agent. The inventors presume that the above-mentioned effects of the present invention are achieved in the above-mentioned manner.
[0010] [Component (A)] Examples of the (A) resin used in this embodiment include rosin resin, acrylic resin, epoxy resin, and phenol resin. These may be used alone or in combination of two or more. Among these, rosin resin or acrylic resin is preferred from the viewpoint of viscosity stability. Examples of the rosin-based resin include rosins and rosin-based modified resins. Examples of the rosins include gum rosin, wood rosin, and tall oil rosin. Examples of the rosin-based modified resin include disproportionated rosin, polymerized rosin, hydrogenated rosin, and derivatives thereof. Examples of the hydrogenated rosin include fully hydrogenated rosin, partially hydrogenated rosin, and hydrogenated products of unsaturated organic acid-modified rosin (also called "hydrogenated acid-modified rosin"), which are modified rosins of unsaturated organic acids (aliphatic unsaturated monobasic acids such as (meth)acrylic acid, aliphatic unsaturated dibasic acids such as α,β-unsaturated carboxylic acids such as fumaric acid and maleic acid, unsaturated carboxylic acids having aromatic rings such as cinnamic acid, etc.). These rosin-based resins may be used alone or in combination of two or more. In addition, from the viewpoint of cleaning properties of flux residue, it is preferable to use at least one of polymerized rosin and hydrogenated acid-modified rosin among these rosin-based resins, and it is more preferable to use polymerized rosin. It is more preferable to use polymerized rosin in combination with other rosin-based resins (hydrogenated acid-modified rosin, formylated rosin, modified rosin, or the like). The acrylic resin is obtained by polymerizing at least one monomer such as acrylic acid, methacrylic acid, various esters of acrylic acid, various esters of methacrylic acid, crotonic acid, itaconic acid, maleic acid, maleic anhydride, esters of maleic acid, esters of maleic anhydride, acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, vinyl chloride, and vinyl acetate. The acrylic resin is useful in that it can prevent cracks from occurring in the flux residue even in an environment with a large temperature difference and a large thermal shock. Among these acrylic resins, acrylic resins obtained by polymerizing monomers containing methacrylic acid and a monomer having an alkyl group with 2 to 6 carbon atoms, and further acrylic resins obtained by polymerizing monomers containing methacrylic acid and a monomer having an alkyl group with 2 carbon atoms are preferred. Such acrylic resins are preferred in that they suppress the stickiness of the flux residue (flux solidified product) formed and have a good crack suppression effect.
[0011] The amount of the (A) component is preferably 30% by mass or more and 70% by mass or less, and more preferably 35% by mass or more and 60% by mass or less, based on 100% by mass of the flux composition. If the amount of the (A) component is more than the lower limit, the oxidation of the copper foil surface of the soldering land is prevented, making the surface more easily wetted with molten solder, so that the so-called solderability can be improved and solder balls can be sufficiently suppressed. Also, if the amount of the (A) component is less than the upper limit, the amount of flux residue can be sufficiently suppressed.
[0012] [(B) Component] The (B) activator used in this embodiment must contain (B1) a dicarboxylic acid having from 9 to 22 carbon atoms. This (B1) component can improve the cleaning properties with an aqueous cleaner without deteriorating the ionic cleanliness. Examples of the (B1) component include azelaic acid, sebacic acid, dodecanedioic acid, eicosane diacid, and 8,13-dimethyl-8,12-eicosadienedioic acid. These may be used alone or in combination of two or more. From the viewpoint of the balance between ionic cleanliness and other physical properties, it is particularly preferable to use eicosane diacid in combination with other (B1) components.
[0013] The blending amount of the (B1) component is preferably 0.1% by mass to 12% by mass, more preferably 0.5% by mass to 10% by mass, even more preferably 1% by mass to 8% by mass, and particularly preferably 2% by mass to 7% by mass, based on 100% by mass of the flux composition. If the blending amount of the (B1) component is equal to or more than the lower limit, the solderability tends to be improved without deteriorating the ionic cleanliness, while if it is equal to or less than the upper limit, the insulating properties of the flux composition tend to be maintained.
[0014] Component (B) may further contain (B2) a dicarboxylic acid having three carbon atoms (malonic acid). Since component (B2) has a low decomposition temperature, it does not remain in the flux residue and does not deteriorate the ionic cleanliness even if used.
[0015] The blending amount of the (B2) component is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.2% by mass or more and 4% by mass or less, and particularly preferably 0.3% by mass or more and 3% by mass or less, based on 100% by mass of the flux composition. If the blending amount of the (B2) component is equal to or more than the lower limit, the wettability in the low temperature range tends to be further improved, while if it is equal to or less than the upper limit, the insulating properties of the flux composition tend to be maintained.
[0016] Component (B) may further contain an organic acid other than components (B1) and (B2) (hereinafter sometimes referred to as component (B3)). However, when component (B3) is used, it is preferable to pay attention to the fact that dicarboxylic acids other than components (B1) and (B2) may deteriorate the ionic cleanliness. Examples of the (B3) component include monocarboxylic acids, dicarboxylic acids other than the (B1) and (B2) components, and other organic acids. These may be used alone or in combination of two or more. Monocarboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, capric acid, lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, tuberculostearic acid, arachidic acid, behenic acid, lignoceric acid, and glycolic acid. Dicarboxylic acids include adipic acid, suberic acid, dimer acid, tartaric acid, and diglycolic acid. Other organic acids include trimer acid, levulinic acid, lactic acid, acrylic acid, benzoic acid, salicylic acid, anisic acid, citric acid, and picolinic acid, etc. Among these, it is more preferable to use picolinic acid.
[0017] When the (B3) component is used, its amount is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.2% by mass or more and 5% by mass or less, and particularly preferably 0.3% by mass or more and 3% by mass or less, based on 100% by mass of the flux composition. If the (B3) component is added in an amount equal to or more than the lower limit, the activation action tends to be improved, whereas if the amount is equal to or less than the upper limit, the insulating properties of the flux composition tend to be maintained.
[0018] In addition to the components (B1) to (B3), the component (B) may further contain another activator (hereinafter also referred to as the component (B4)) within the scope of the present invention. Examples of the component (B4) include halogen-based activators and amine-based activators. However, the total amount of the components (B1) to (B3) is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the component (B).
[0019] The blending amount of the (B) component is preferably 1% by mass or more and 20% by mass or less, more preferably 2% by mass or more and 15% by mass or less, and particularly preferably 3% by mass or more and 13% by mass or less, based on 100% by mass of the flux composition. If the blending amount of the (B) component is equal to or more than the lower limit, the activation action tends to be improved, whereas if it is equal to or less than the upper limit, the insulating property of the flux composition tends to be maintained.
[0020] [(C) component] The (C) solvent used in this embodiment must contain (C1) a solvent having a boiling point of 250° C. or lower and a melting point of 15° C. or higher. The (C1) component can improve the effect of suppressing voids. Examples of the (C1) component include 1,4-butanediol (melting point 19°C, boiling point 228°C), 1,6-hexanediol (melting point 42°C, boiling point 250°C), 2,2-dimethyl-1,3-propanediol (melting point 128°C, boiling point 210°C), and 2,5-dimethyl-2,5-hexanediol (melting point 89°C, boiling point 214°C). These may be used alone or in combination of two or more. From the viewpoint of the void suppression effect, it is preferable to use two or more of these in combination, and it is particularly preferable to use 1,4-butanediol and 2,5-dimethyl-2,5-hexanediol in combination.
[0021] The blending amount of the (C1) component must be 10% by mass or more and 50% by mass or less, based on 100% by mass of the (C) component. If the blending amount of the (C1) component is less than the lower limit, the generation of voids cannot be suppressed. On the other hand, if the blending amount of the (C1) component is more than the upper limit, the stability over time decreases. From the same viewpoint, the blending amount of the (C1) component is preferably 11% by mass or more and 35% by mass or less, more preferably 13% by mass or more and 30% by mass or less, even more preferably 15% by mass or more and 25% by mass or less, and particularly preferably 15% by mass or more and 20% by mass or less, based on 100% by mass of the (C) component.
[0022] The (C) component preferably contains (C2) a solvent having a melting point of less than 15° C. As the (C2) component, a known solvent can be appropriately used. As such a solvent, it is preferable to use a solvent having a boiling point of 170° C. or more. Examples of such solvents include diethylene glycol, dipropylene glycol, triethylene glycol, hexylene glycol, 1,5-pentanediol, 2,5-dimethyl-2,5-hexanediol, methyl carbitol, butyl carbitol, 2-ethylhexyl diglycol (EHDG), phenyl glycol, diethylene glycol monohexyl ether (hexyl diglycol, DEH), tetraethylene glycol dimethyl ether, and dibutyl maleic acid. Among these, 2,5-dimethyl-2,5-hexanediol is preferred from the viewpoint of printability. These may be used alone or in combination of two or more.
[0023] The blending amount of the (C) component is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 40% by mass or less, based on 100% by mass of the flux composition. When the blending amount of the solvent is within the above range, the viscosity of the obtained solder composition can be appropriately adjusted to an appropriate range.
[0024] [(D) component] As the (D) thixotropic agent used in this embodiment, a known thixotropic agent can be appropriately used. This (D) component can suppress sagging during printing or heating. Examples of the thixotropic agent used here include hardened castor oil, amides, kaolin, colloidal silica, organic bentonite, and glass frit. Among these, amides are preferred from the viewpoint of suppressing sagging. These may be used alone or in combination of two or more.
[0025] The blending amount of the (D) component is preferably 2% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, and particularly preferably 5% by mass or more and 10% by mass or less, based on 100% by mass of the flux composition. If the blending amount is equal to or more than the lower limit, sufficient thixotropy is obtained, sagging tends to be suppressed, and ionic cleanliness tends to be improved. On the other hand, if the blending amount is equal to or less than the upper limit, thixotropy is not too high, printing defects tend not to occur, and cleaning properties with aqueous cleaners tend to be improved.
[0026] [Polyisobutylene] From the viewpoint of a balance between ionic cleanliness and cleaning property with an aqueous cleaner, the flux composition according to the present embodiment preferably further contains polyisobutylene. The molecular weight of polyisobutylene is preferably 1000 to 60000, more preferably 2000 to 50000, and particularly preferably 3000 to 40000. The more the amount of polyisobutylene is increased, the more the ionic cleanliness can be improved. On the other hand, the less the amount of polyisobutylene is decreased, the more the cleaning property with an aqueous cleaner can be improved. From this viewpoint, when polyisobutylene is used, the amount of polyisobutylene is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, and particularly preferably 1% by mass or more and 3% by mass or less, based on 100% by mass of the flux composition.
[0027] [Antioxidants] From the viewpoint of solder melting property, the flux composition according to the present embodiment preferably further contains an antioxidant. As the antioxidant used here, a known antioxidant can be appropriately used. Examples of the antioxidant include sulfur compounds, hindered phenol compounds, and phosphite compounds. Among these, hindered phenol compounds are preferred.
[0028] Examples of the hindered phenol compound include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis(3-tert-butyl-4-hydroxy-5-methylbenzenepropanoic acid)ethylene bis(oxyethylene), N,N'-bis[2-[2-(3,5-di-tert-butyl-4-hydroxyphenyl)ethylcarbonyloxy]ethyl]oxamide, and N,N'-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine.
[0029] When an antioxidant is used, its content is preferably 0.1% by mass or more and 5% by mass or less with respect to 100% by mass of the flux composition. If the content of the antioxidant is equal to or more than the lower limit, the solder melting property tends to be improved, whereas if it is equal to or less than the upper limit, the insulating property of the flux composition tends to be maintained.
[0030] [Other ingredients] In addition to the (A), (B), (C), and (D) components, polyisobutylene, and antioxidant, other additives may be added to the flux composition used in this embodiment as necessary. Examples of other additives include imidazole compounds, antifoaming agents, modifiers, matting agents, and foaming agents. The amount of these additives is preferably 0.01% by mass or more and 5% by mass or less with respect to 100% by mass of the flux composition.
[0031] [Solder composition] Next, the solder composition according to the present embodiment will be described. The solder composition according to the present embodiment contains the flux composition according to the present embodiment described above and the solder powder (E) described below. The amount of the flux composition is preferably 5% by mass or more and 35% by mass or less, more preferably 7% by mass or more and 15% by mass or less, and particularly preferably 8% by mass or more and 12% by mass or less, relative to 100% by mass of the solder composition. When the amount of the flux composition is less than 5% by mass (when the amount of the solder powder exceeds 95% by mass), the flux composition as a binder is insufficient, so that it tends to be difficult to mix the flux composition and the solder powder. On the other hand, when the amount of the flux composition is more than 35% by mass (when the amount of the solder powder is less than 65% by mass), when the obtained solder composition is used, it tends to be difficult to form a sufficient solder joint.
[0032] [(E) component] The solder powder (E) used in this embodiment is preferably made of only lead-free solder powder, but may be lead-containing solder powder. The solder alloy in this solder powder preferably contains at least one selected from the group consisting of tin (Sn), copper (Cu), zinc (Zn), silver (Ag), antimony (Sb), lead (Pb), indium (In), bismuth (Bi), nickel (Ni), cobalt (Co) and germanium (Ge). The solder alloy in the solder powder is preferably an alloy mainly composed of tin, more preferably containing tin, silver and copper, and may further contain at least one of antimony, bismuth and nickel as an additive element. Here, lead-free solder powder refers to a powder of solder metal or alloy to which no lead is added. However, the presence of lead as an unavoidable impurity in the lead-free solder powder is permitted, but in this case, the amount of lead is preferably 300 ppm by mass or less.
[0033] Specific examples of alloy systems for lead-free solder powder include Sn-Ag-Cu systems, Sn-Cu systems, Sn-Ag systems, Sn-Bi systems, Sn-Ag-Bi systems, Sn-Ag-Cu-Bi systems, Sn-Ag-Cu-Ni systems, Sn-Ag-Cu-Bi-Sb systems, Sn-Ag-Bi-In systems, and Sn-Ag-Cu-Bi-In-Sb systems.
[0034] The average particle size of component (E) is usually 1 μm or more and 40 μm or less, but from the viewpoint of compatibility with electronic boards having narrow pitches of solder pads, it is more preferably 1 μm or more and 35 μm or less, even more preferably 2 μm or more and 35 μm or less, and particularly preferably 3 μm or more and 32 μm or less. The average particle size can be measured by a dynamic light scattering type particle size measuring device.
[0035] [Method of manufacturing solder composition] The solder composition of this embodiment can be produced by blending the above-described flux composition and the above-described (E) solder powder in the above-described predetermined ratio, and stirring and mixing them.
[0036] [Electronic board] Next, the electronic board according to the present embodiment will be described. The electronic board according to the present embodiment is characterized by having a soldered portion using the solder composition according to the present embodiment. The electronic board according to the present embodiment can be manufactured by mounting electronic components on an electronic board (such as a printed wiring board) using the solder composition. Examples of the coating device used here include a screen printer, a metal mask printer, a dispenser, and a jet dispenser. In addition, electronic components can be mounted on an electronic board by a reflow process in which electronic components are placed on the solder composition applied by an application device and heated under specified conditions in a reflow furnace to mount the electronic components on a printed wiring board.
[0037] In the reflow process, an electronic component is placed on the solder composition and heated in a reflow furnace under predetermined conditions. This reflow process allows a sufficient solder joint to be formed between the electronic component and the printed wiring board. As a result, the electronic component can be mounted on the printed wiring board. The reflow conditions may be appropriately set according to the melting point of the solder. For example, the preheat temperature is preferably 140°C or higher and 200°C or lower, and more preferably 150°C or higher and 160°C or lower. The preheat time is preferably 60 seconds or higher and 120 seconds or lower. The peak temperature is preferably 230°C or higher and 270°C or lower, and more preferably 240°C or higher and 255°C or lower. The holding time at a temperature of 220°C or higher is preferably 20 seconds or higher and 60 seconds or lower.
[0038] It is preferable that the electronic substrate after the reflow process has a good ionic cleanliness. That is, the ionic cleanliness is 1.60 μg NaCl / cm 2 Preferably, it is less than 1.40 μg NaCl / cm 2 The ionic cleanliness can be measured by the method described in the Examples below.
[0039] After the reflow process, a cleaning process is preferably carried out in which flux residue on the electronic substrate is cleaned using a water-based cleaner. The cleaning method may be a dipping method, a jet method, or the like. For example, in the immersion method, the electronic substrate is immersed in a water-based cleaning agent, and ultrasonic waves may be applied at this time. As the water-based cleaner, any known water-based cleaner for flux residue can be used. Here, water-based refers to a cleaner whose main component is water (water is 50% by mass or more). Commercially available products include "VIGON US" made by Zestron Japan Co., Ltd. and "Pine Alpha ST-180K" made by Arakawa Chemical Industries Co., Ltd. The temperature of the aqueous cleaner during cleaning is, for example, 30° C. or higher and 70° C. or lower. The cleaning time is, for example, from 1 minute to 10 minutes. After cleaning with the aqueous cleaner, rinsing may be performed. The conditions for rinsing are not particularly limited, and the rinsing may be performed with water at 20° C. to 50° C. for 0.5 minutes to 5 minutes. Rinsing may be performed two or more times.
[0040] Furthermore, the flux composition, the solder composition, and the electronic board according to the present embodiment are not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. For example, in the electronic substrate, the printed wiring board and the electronic component are bonded by a reflow process, but this is not limiting. For example, instead of the reflow process, the printed wiring board and the electronic component may be bonded by a process of heating the solder composition using laser light (laser heating process). In this case, the laser light source is not particularly limited and can be appropriately adopted depending on the wavelength that matches the absorption band of the metal. Examples of the laser light source include solid lasers (ruby, glass, YAG, etc.), semiconductor lasers (GaAs, InGaAsP, etc.), liquid lasers (dye, etc.), and gas lasers (He-Ne, Ar, CO 2 , and excimers). EXAMPLES
[0041] The present invention will now be described in more detail with reference to examples and comparative examples, but the present invention is not limited to these examples. The materials used in the examples and comparative examples are shown below. (Component (A)) Rosin-based resin A: Polymerized rosin, product name "Chinese Polymerized Rosin", manufactured by Arakawa Chemical Industries, Ltd. Rosin resin B: Acrylic acid modified hydrogenated rosin, product name "Pine Crystal KE-604", manufactured by Arakawa Chemical Industries Co., Ltd. Rosin-based resin C: Formylated rosin, trade name "FORAL-AX", manufactured by Eastman Chemical Company Rosin-based resin D: Special modified rosin, product name "Haritac FG-90", manufactured by Harima Chemicals Co., Ltd. ((B1) component) Dicarboxylic acid A: Sebacic acid Dicarboxylic acid B: Dodecanedioic acid Dicarboxylic acid C: Eicosanedioic acid, trade name "SL-20", manufactured by Okamura Oil Mills Dicarboxylic acid D: 8,13-dimethyl-8,12-eicosadienedioic acid, trade name "IPU-22", manufactured by Okamura Oil Mills ((B2) component) Dicarboxylic acid E: Malonic acid (Component (B3)) Organic acid: Picolinic acid ((C1) component) Solvent A: 1,4-butanediol (melting point 19°C, boiling point 228°C) Solvent B: 1,6-Hexanediol (melting point 42°C, boiling point 250°C) Solvent C: 2,2-dimethyl-1,3-propanediol (melting point 128°C, boiling point 210°C) Solvent D: 2,5-dimethyl-2,5-hexanediol (melting point 89°C, boiling point 214°C) ((C2) component) Solvent E: Hexyl diglycol (melting point -40°C, boiling point 259°C) Solvent F: 2-ethylhexyl diglycol (melting point -82°C, boiling point 272°C) Solvent G: Dibutyl maleate (melting point -85℃, boiling point 280℃) Solvent H: Tetraethylene glycol dimethyl ether (melting point -27°C, boiling point 275°C) ((D) component) Thixotropic agent A: Trade name "Himako", manufactured by KF Trading Co., Ltd. Thixotropic agent B: Ethylene bis hydroxystearic acid amide, product name "Slipax H", manufactured by Mitsubishi Chemical Corporation Thixotropic agent C: Hexamethylene hydroxystearic acid amide, product name "Slipax ZHH", manufactured by Mitsubishi Chemical Corporation (Other ingredients) Imidazole: 2-ethyl-4-methylimidazole Antioxidant: bis(3-tert-butyl-4-hydroxy-5-methylbenzenepropanoate) ethylene bis(oxyethylene), product name "Irganox 245", manufactured by BASF Polyisobutylene: Polyisobutylene, trade name "Tetrax 3T", manufactured by ENEOS Corporation (component (E)) Solder powder: alloy composition is Sn-3.0Ag-0.5Cu, particle size distribution is 20-38μm (equivalent to type 4 of IPC-J-STD-005A), solder melting point is 217-220℃
[0042] [Example 1] 30 mass% rosin-based resin A, 15 mass% rosin-based resin B, 4 mass% dicarboxylic acid C, 0.5 mass% dicarboxylic acid E, 0.5 mass% organic acid, 3 mass% antioxidant, 1.5 mass% imidazole, 2 mass% polyisobutylene, 4 mass% solvent A, 3 mass% solvent D, 30 mass% solvent E, 0.5 mass% thixotropic agent A, and 6 mass% thixotropic agent B were charged into a container and mixed using a planetary mixer to obtain a flux composition. Thereafter, 12% by mass of the obtained flux composition and 88% by mass of the solder powder (total of 100% by mass) were placed in a container and mixed with a planetary mixer to prepare a solder composition.
[0043] [Examples 2 to 8] A solder composition was obtained in the same manner as in Example 1, except that the materials were mixed according to the composition shown in Table 1. [Comparative Examples 1 to 6] A solder composition was obtained in the same manner as in Example 1, except that the materials were mixed according to the composition shown in Table 1. [Examples 9 to 25] A solder composition was obtained in the same manner as in Example 1, except that the materials were mixed according to the composition shown in Table 2.
[0044] <Evaluation of solder composition> The solder compositions were evaluated (ionic cleanliness, flux cleaning ability, voids, and stability over time) by the following methods. The results are shown in Tables 1 and 2. The amount (mass%) of component (C1) in component (C) is also shown in Tables 1 and 2. (1) Ionic cleanliness A solder composition was printed on a JIS2-type comb-shaped substrate, and the solder composition was melted in a reflow furnace (manufactured by Tamura Manufacturing Co., Ltd.) to obtain a substrate for evaluation. The reflow conditions were a preheat temperature of 130 to 180°C (about 100 seconds), a time at a temperature of 220°C or higher for about 60 seconds, a peak temperature of 240°C, and a nitrogen atmosphere with an oxygen concentration of 1000 ppm. The substrate for evaluation was set in an omegameter, and a 75% IPA solution was injected into the test cell as a test liquid, and the change in the resistance value of the test liquid was obtained to calculate the eluted ions of the specimen. The amount of eluted ions was converted into a NaCl equivalent value to be the ionic cleanliness. The ionic cleanliness was evaluated according to the following criteria. ○: Ionic cleanliness is 1.40μgNaCl / cm 2 is less than. △: Ionic cleanliness is 1.40μgNaCl / cm 2 More than 1.60μgNaCl / cm 2 is less than. ×: Ionic cleanliness is 1.60 μg NaCl / cm 2 That's all. (2) Cleanability A solder composition was printed on a substrate capable of mounting chip components, chip components (size: 1.6 mm x 0.8 mm) were mounted, and the solder composition was melted and soldered in a reflow furnace (manufactured by Tamura Corporation) to obtain a substrate for evaluation. The preheat temperature was 130 to 180°C (approximately 100 seconds), the time at a temperature of 220°C or higher was approximately 60 seconds, the peak temperature was 240°C, and the atmosphere was nitrogen with an oxygen concentration of 1000 ppm. Next, the obtained evaluation substrate was immersed in a container containing a water-based cleaning agent (Zestron Japan's "VIGON US", 20% concentration) and cleaned with ultrasonic waves (liquid temperature: 60°C, cleaning time: 5 minutes). After that, the liquid was removed with an air knife, and the substrate was immersed in a container containing pure water at room temperature for a first rinse (rinsing time: 1 to 2 minutes), and further immersed in a container containing pure water at 45°C for a second rinse (rinsing time: 1 to 2 minutes). After that, the liquid was removed with an air gun, and the substrate was dried in a hot air drying furnace (furnace temperature: 70°C) for 10 minutes. After cleaning with the aqueous cleaner, all chips were removed from the evaluation board and the presence or absence of flux residue under the chips was observed. The number of chips with residual flux and the ratio to the total number of chips (residual ratio) were then measured, and the cleaning performance was evaluated based on the residual ratio according to the following criteria. ◯: The residual ratio is 10% or more and less than 20%. △: The residual ratio is 20% or more and less than 50%. ×: The residual ratio is 50% or more. (3) Void A solder composition was printed on a board capable of mounting QFN components, and a Sn-plated QFN was mounted on it. The solder composition was melted in a reflow furnace (manufactured by Tamura Corporation) and soldered to obtain a board for evaluation. The reflow conditions were a preheat temperature of 130 to 180°C (approximately 100 seconds), a time at a temperature of 220°C or higher for approximately 60 seconds, a peak temperature of 240°C, and air. An X-ray photograph was taken of the joint of the evaluation board, and the void area [(void area ÷ land area) × 100] (unit: %) of the lower electrode (5.9 mm × 5.9 mm) was measured. The average value of the void area and the maximum value of the void area were then calculated, and the voids were evaluated according to the following criteria. Note that if the maximum value of the void area is high, it can be said that the voids vary widely. -Average void area ◯: The average void area is 25% or less. △: The average void area is more than 25% and 35% or less. ×: The average void area is more than 35%. Maximum void area ◯: The maximum void area is 35% or less. △: The maximum value of the void area is more than 35% and 45% or less. ×: The maximum void area is more than 45%. (4) Stability over time The viscosity was measured using the solder composition as a sample. The sample was then placed in a sealed container, put into a thermostatic bath at 30°C, and stored for 14 days, and the viscosity of the stored sample was measured. The difference (η2-η1) between the initial viscosity value (η1) and the viscosity value (η2) after 14 days of storage at 30°C was calculated, and the viscosity increase rate [{(η2-η1) / η1}×100] (unit: %) was calculated. The viscosity was measured using a spiral type viscosity measurement (Malcom, PCU-II type, measurement temperature: 25°C, rotation speed: 10 rpm, after stirring for 3 minutes). ◯: The viscosity increase rate is less than 10%. △: The viscosity increase rate is 10% or more and less than 15%. ×: The viscosity increase rate is 15% or more.
[0045] [Table 1]
[0046] [Table 2]
[0047] As is clear from the results shown in Tables 1 and 2, the solder compositions of the present invention (Examples 1 to 25) were confirmed to be excellent in all aspects of ionic cleanliness, flux cleaning ability, voids, and stability over time. Therefore, it was confirmed that the solder composition of the present invention has a good ionic cleanliness, is excellent in cleaning ability for flux residues with an aqueous cleaner, and can sufficiently suppress voids. [Industrial Applicability]
[0048] The flux composition and solder composition of the present invention can be suitably used as a technique for mounting electronic components on electronic substrates such as printed wiring boards of electronic devices.
Claims
1. A flux composition comprising: (A) a resin; (B) an activator; (C) a solvent; and (D) a thixotropic agent, The component (B) contains (B1) a dicarboxylic acid having from 9 to 22 carbon atoms, The component (B1) contains a dicarboxylic acid having 20 carbon atoms, The component (C) contains (C1) a solvent having a boiling point of 250° C. or less and a melting point of 15° C. or more, The blending amount of the (C1) component is 10% by mass or more and 50% by mass or less with respect to 100% by mass of the (C) component. Flux composition.
2. A flux composition comprising: (A) a resin; (B) an activator; (C) a solvent; and (D) a thixotropic agent, The component (B) contains (B1) a dicarboxylic acid having from 9 to 22 carbon atoms, The component (C) contains (C1) a solvent having a boiling point of 250° C. or less and a melting point of 15° C. or more, the component (C1) contains at least one selected from the group consisting of 1,4-butanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, and 2,5-dimethyl-2,5-hexanediol; The blending amount of the (C1) component is 10% by mass or more and 50% by mass or less with respect to 100% by mass of the (C) component. Flux composition.
3. A flux composition comprising (A) a resin, (B) an activator, (C) a solvent, (D) a thixotropic agent, and polyisobutylene, The component (B) contains (B1) a dicarboxylic acid having from 9 to 22 carbon atoms, The component (C) contains (C1) a solvent having a boiling point of 250° C. or less and a melting point of 15° C. or more, The blending amount of the (C1) component is 10% by mass or more and 50% by mass or less with respect to 100% by mass of the (C) component. Flux composition.
4. The flux composition according to any one of claims 1 to 3, The blending amount of the (D) component is 2 mass% or more and 20 mass% or less with respect to 100 mass% of the flux composition, Flux composition.
5. A flux composition according to any one of claims 1 to 3, and (E) a solder powder. Solder composition.
6. A soldered portion comprising the solder composition according to claim 5. Electronic board.
Citation Information
Patent Citations
Preparation of entangled cocoon filament
JP1983087330A
Solder composition and electronic substrate
JP2018034190A
Solder composition and electronic substrate
JP2018161674A
Solder composition and electronic substrate
JP2019042805A
Flux and solder paste
JP2019122994A